SYSTEMATIC ANALYSIS OF THE APPLICATION OF FRAUD TRIANGLE THEORY IN ACCOUNTING FRAUD DETECTION: A LITERATURE REVIEW OF PRESSURE, OPPORTUNITY, AND RATIONALISATION - Juliana Waromi; Siti Rofingatun; Dytha M Nababan (Journal of Economic, Bussines and Accounting (COSTING), 2025)
The high level of accounting fraud in financial reporting necessitates a deeper understanding of its causes. This study aims to analyse the application of the Fraud Triangle Theory as a conceptual framework for detecting and explaining fraudulent behaviour. The method used is Systematic Literature Review (SLR), which is a type of qualitative research. The population in this study consists of scientific publications discussing the variables of the Fraud Triangle, namely pressure, opportunity, and rationalisation, using purposive sampling based on specific inclusion and exclusion criteria. A total of 25 relevant articles were selected from various reputable databases such as Scopus, ScienceDirect, SpringerLink, Emerald Insight, and SINTA. This study was conducted over three months from March to May 2025. The synthesis results indicate that pressure and opportunity are the most consistent factors driving fraud, while rationalisation tends to be difficult to measure and yields varying results. Additionally, there is a trend toward developing the theory into advanced models such as the Fraud Diamond and Fraud Pentagon. The study also found that integrating the Fraud Triangle with artificial intelligence-based technology has the potential to improve fraud detection in the digital age. These findings have important implications for strengthening internal control systems, anti-corruption policies, and the development of theoretical and practical instruments for accounting fraud prevention